BIMBINGAN BAGI ANAK CERDAS BERBAKAT DI SEKOLAH DASAR GMIT 05 ADANG - Hana K. Lamma Koly; Devita T. Mabilehi, Sely Djaha, Yessy Mata, Petrus Mau Tellu Dony, Jon Abraham Lalang Yame, Imanuel (CV. Adiba Aisha Amira, 2025)
The purpose of this study is to examine guidance services for gifted and intelligent children at GMIT 05 Adang Elementary School, Adang Buom Village, Teluk Mutiara District, Alor Regency. The research technique used in this study is descriptive qualitative, interviews with the homeroom teacher of class III, Bapak Mustapa Kiang S. Pd, and students of class III at GMIT 05 Adang Elementary School, Adang Buom Village, Teluk Mutiara District, Alor Regency. The results of this study indicate that the class teacher has provided guidance services in class and students have also received guidance services at GMIT 05 Adang Elementary School, class III.